Choice and wellbeing in informal care - Hareth Al-Janabi; Fiona Carmichael; Jan Oyebode (University of Birmingham, Birmingham Business School, 2016)
Choice' is increasingly pursued as a goal of social policy. However the degree to which choice is exercised when entering an informal care role is open to debate. In this study of UK carers, we examined whether caring was perceived as a free choice, and what the consequence of choice was for carers' wellbeing. Our data were derived from responses to a postal survey conducted in a large British city. One thousand one hundred respondents reported providing care to a close person and of these, 72% answered a further set of questions about caregiving and about their own well-being. We found that informal care was generally perceived to be a free choice, albeit in most cases, a choice that was constrained by duty, financial or social resources. Having a sense of free choice in entering care was strongly and positively associated with wellbeing. The positive impact on wellbeing persisted across different measures of wellbeing and when controlling for socio-demographic characteristics and the nature of the caring role. Further work is needed to better understand the modifiable aspects of choice for carers. Nonetheless, this study suggests that enabling individuals to have more choice in their caring roles may improve their lives.
Keywords: 330; choice; informal care; motivation; wellbeing; UK